The splicing of U12-type introns can be a rate-limiting step in gene expression. - Patel, A.A.; McCarthy, M.; Steitz, J.A. (The EMBO Journal, 2002)
Some protein-coding genes in metazoan genomes contain a minor class of introns that are excised by a distinct, low-abundance spliceosome. We have developed a quantitative RT-PCR assay that allows comparison of the relative rates of intron removal from the transcripts present in a pre-mRNA population. We show that the U12-type introns are more slowly spliced than the major-class (U2-type) introns from three endogenous pre-mRNAs in human tissue culture cells. In Drosophila melanogaster S2 cells, using minigene constructs designed to produce nearly identical mRNAs, we observe increased expression of fluorescent protein and mature mRNA upon mutation of a U12-type to a U2-type intron. These results provide evidence that the level of gene expression in vivo is lowered by the presence of a U12-type intron and implicate the U12-type spliceosome as a target in the post-transcriptional regulation of gene expression.